The socio-cultural contexts of development communication at the Tswaing Crater - C.W. Malan; A. Grossberg (Communicare)
The main discussion on the process of development communication as a core component of a sustainable development project at the Tswaing Crater Museum near Pretoria. The arlicle initially surveys some local studies and lessons leamed in an effort to contextua/ise the Tswaing project. Various approaches, such as Participatory C;ommunication, and Development Support Communication are discussed and related to communication structures for the project. New forces in democratisation have contributed to the crucial role of concepts such as participation, empowerment and emancipation. These approaches rely on normative goals and standards set by host communities in the development of a community's cultural identity, and act as a vehicle for people's self expression. Socia-cultural contexts of the developmental and communication process are therefore specifically discussed. Finally lessons leamed provide a means of recommending possible solutions to development communication problems.